The Resurgence of Fundamentalism in the Southern Baptist Convention A History from 1960 to 1979. - Faught, Jerry (Lewiston : The Edwin Mellen Press, 2014)
The Southern Baptist Convention (SBC) experienced an intense struggle for control of the ideological direction of its denomination in the 1960s and 1970s. This book examines how the Conservative movement within the denomination took aim at reorienting the denomination away from its perceived liberal course and toward a clear and unquestioned affirmation of biblical inerrancy.This study investigates both the Elliott and Broadman Controversies. Since events do not take place in a vacuum, the conflicts are set in their respective historical contexts, both socio-cultural and religious. This projec.
The Resurgence of Fundamentalism in the Southern Baptist Convention: A History from 1960-1979; Copyright Page; Dedication; Table of Contents; Foreword; Introduction; Chapter I; Chapter II; Chapter III; Chapter IV; Chapter V; Conclusion; Bibliography; Index
Description based upon print version of record.
Keywords: Southern Baptist Convention -- History; Fundamentalism; RELIGION / Christianity / Baptist; Electronic books